A Comparative Study between Operative Ultrasonography and Perioperative Cholangiography in Screening of The Common Bile Duct for Stones During Laparoscopic Cholecystectomy - Ahmed Abdelhakim; Alsayed Hamdy; Ahmed Ahmed; Ahmed Abo Elfottoh (International Journal of Medical Arts, 2023)
Background: The routine uses of intraoperative cholangiography [IOC] is still controversial. Some authors support routine IOC, while others favor selective IOC. The operative ultrasonography [OUS] probe provides a new modality for evaluating biliary anatomy and detection of Choledocholithiasis during laparoscopic cholecystectomy. It is considered a faster, safer, and non-invasive technique.Aim of the Study: This study aims to compare the accuracy of operative ultrasonography [OUS] and IOC in the detection of common bile duct stones during laparoscopic cholecystectomy.Patients and Methods: This prospective comparative study included 50 patients who underwent laparoscopic cholecystectomies with or without bile duct exploration, which was done at El-Hussein University Hospital in the period from March 2018 to December 2019. Operative laparoscopic ultrasonography was performed followed by an operative cholangiogram. Bile ducts were explored if CBD stones were seen and the patients were followed up by clinical evaluation, laboratory investigations, and abdominal ultrasound within one month from surgery.Results: The IOUS timing which was the time after identification of the cystic duct and artery till the start of IOC, was significantly lower than the IOC Timing which was the time After IOUS till clipping of the proximal part of the cystic duct. The sensitivity and specificity of IOUS for detection of CBD stone was 100%, and 94.4% respectively in comparison to 100% sensitivity and specificity in the IOC.Conclusion: During the exploration of the CBD stones, the IOUS is just as sensitive and specific as the IOC. It's less invasive than IOC and can be done quickly by any skilled surgeon, so during a laparoscopic cholecystectomy, IOUS can reliably replace IOC.